Estimating building construction costs: analysis of the processbased budget model (POP Model) - Falcón, R.; Montes Delgado, M. Victoria; Ramírez, A. (Revista Ingeniería de Construcción, 2016)
The recent economic crisis suffered by the Spanish construction sector has brought to light its excessive vulnerability to fluctuations in the real estate market. Overcoming this situation requires to innovate the sector in order to increase its efficiency. A large amount of researches in Spain focus on the improvement of the environmental efficiency of construction works, but only a few of them deal with its economic efficiency. The current study arises from the importance of the latter in order to achieve a comprehensive sustainability in construction. We introduce a process-based budget model, the POP model, whose most significant strength is the direct inclusion of all costs incurred at the building production site. In this way, process-based estimates expose with transparence and accuracy the real nature of the projected works, contributing to improve their economic management.